INDEKS MASSA TUBUH BERPENGARUH TERHADAP USIA MENARCHE PADA SISWI KELAS 5 DAN 6 DI SDN 01 WIYUNG SURABAYA - Putri, Fitria Rakhmawati; Wesiana, Wesiana (Universitas Nahdlatul Ulama Surabaya, 2014)
Menarche is the first menstruation confirming the sexual maturity in adolescents. Nearly half of the female students having menarche earlier at the age of ? 10 years are overweight. Therefore, the purpose of this study was to find out the correlation between Body Mass Index (BMI) and age at menarche in the fifth and sixth-grade female students studying at SDN 01 Wiyung Surabaya (State Elementary School).   The type of study was analytic. The population involved all of the fifth and sixth-grade female students studying at the elementary school mentioned above having menarche in the last month, totally 17 respondents which were taken as the samples by using total sampling technique. The independent variable was BMI, whereas the dependent one was age at menarche. The data were collected by doing interview and observation. Moreover, they were analyzed by using Spearman?s Rank test with the significance level ?  = 0.05.  The result of study showed that nearly all of the respondents (76.5%) had BMI with obesity and early menarche. Furthermore, the result of Spearman Rank test showed that p = 0.003 and ? = 0.05 which meant that p < ? so that H0 was rejected stating that there was a correlation between the Body Mass Index (BMI) and age at menarche in the fifth and sixth-grade female students studying at SDN 01 Wiyung Surabaya.  The conclusion of study was that the adolescents having higher BMI tend to have menarche earlier. Therefore, the adolescents are expected tokeep maintain the menu of balanced foods.